Rapamycin-upregulated miR-29b promotes mTORC1-hyperactive cell growth in TSC2-deficient cells by downregulating tumor suppressor retinoic acid receptor β (RARβ) - Liu, Heng-Jia (Oncogene, 2019)
miR-29b has been identified as a rapamycin-induced microRNA (miRNA) in Tsc2-deficient, mTORC1-hyperactive cells. The biological significance of this induction of miR-29b is unknown. We have found that miR-29b acts as an oncogenic miRNA in Tsc2-deficient cells: inhibition of miR-29b suppressed cell proliferation, anchorage-independent cell growth, cell migration, invasion, and the growth of Tsc2-deficient tumors in vivo. Importantly, the combination of miR-29b inhibition with rapamycin treatment further inhibited these tumor-associated cellular processes. To gain insight into the molecular mechanisms by which miR-29b promotes tumorigenesis, we used RNA sequencing to identify the tumor suppressor retinoid receptor beta (RARβ) as a target gene of miR-29b. We found that miR-29b directly targeted the 3′UTR of RARβ. Forced expression of RARβ reversed the effects of miR-29b overexpression in proliferation, migration, and invasion, indicating that it is a critical target. miR-29b expression correlated with low RARβ expression in renal clear cell carcinomas and bladder urothelial carcinomas, tumors associated with TSC gene mutations. We further identified growth family member 4 (ING4) as a novel interacting partner of RARβ. Overexpression of ING4 inhibited the migration and invasion of Tsc2-deficient cells while silencing of ING4 reversed the RARβ-mediated suppression of cell migration and invasion. Taken together, our findings reveal a novel miR-29b/RARβ/ING4 pathway that regulates tumorigenic properties of Tsc2-deficient cells, and that may serve as a potential therapeutic target for TSC, lymphangioleiomyomatosis (LAM), and other mTORC1-hyperactive tumors.